Infrastruktur dan Output Perkapita Antar Provinsi di Indonesia - Bayu Kharisma; Vita Nuraeiny (MediaTrend, 2018)
in 2010-2015, Indonesia's economic growth experienced a slowdown, the average economic growth of Indonesia during 2010-2015 was 5.65%. Indonesia's economic growth was influenced by various conditions that developed in the world economy such as declining world commodity prices, high inflation after the price hike of subsidized fuels, and the decline in bank credit due to tightening monetary policy. The purpose of this study is to determine the effect of infrastructure which includes roads, electricity, clean water and ports on per capita output. This study uses a static and dynamic panel data model in 33 provinces in Indonesia during the period 2010-2015. The results of this study indicate that road and port infrastructure has a positive and significant influence on per capita output, while electricity and clean water infrastructure have a positive but insignificant influence. In this regard, the government can take a policy of increasing and building road infrastructure and improving service performance in the form of port loading and unloading productivity.